Impact of Transmission Configuration on Efficiency and Energy Recovery in Electric Vehicles: Published online: 29/01/2026 - Le, Thanh Quang; Nguyen Kim, Bao Hieu; Ly, Vinh Dat; Le, Thanh Phuc; Truong, Quang Linh (Journal of Technical Education Science, 2026)
This study investigates the regenerative energy efficiency of electric vehicles (EVs) equipped with Continuously Variable Transmission (CVT) compared to those utilizing traditional Single-Speed Transmission (SST). The research employs a simulation-based approach using Permanent Magnet Synchronous Motors (PMSMs), which are known for their high efficiency and responsiveness in EV applications. By simulating vehicle dynamics under standardized driving cycles such as the New European Driving Cycle (NEDC) and the Worldwide Harmonized Light Vehicles Test Cycle (WLTC), the study analyzes key performance indicators including regenerative braking force, energy recovery potential, and the battery’s state of charge (SOC). The results reveal that EVs with CVT systems outperform their SST counterparts in terms of energy regeneration, particularly during deceleration and braking phases. CVT not only enables smoother transitions in gear ratios but also maintains optimal operating points for the motor, allowing more effective energy capture during braking. Furthermore, vehicles with CVT demonstrate a more stable SOC profile throughout the driving cycles, contributing to extended battery life and improved driving range. These findings highlight the potential of integrating CVT into EV drivetrains as a strategy to enhance overall efficiency, regenerative performance, and driving safety—making it a promising direction for the development of next-generation electric vehicles.